Extracellular biosynthesis and characterization of gold Nanoparticles using penicillium SPS and studies on Antimicrobial activity - SANDHYA. A; SUVARNALATHA DEVI. P (International Journal of Pharma and Bio Sciences, 2017)
In the present days microbial synthesis of nanoparticles is an eco-friendly approach that correlates with nanotechnology and microbial biotechnology. The present study was aimed to isolate the different soil fungi with ultimate objective of producing antimicrobial nanoparticles. Synthesized gold nanoparticles were characterized using UV-visible spectroscopy, Transmission Electron Microscopy and Fourier Transmission Infra Red FTIR analysis and size and shapes were determined. The gold nanoparticles exhibited maximum absorbance at 550 nm in UV-Vis spectroscopy. TEM showed the gold nanoparticles in the size range from 30 to 50nm with an average size of 45nm.The synthesized gold nanoparticles were exhibited an excellent antibacterial activities against both gram negative and gram positive pathogenic bacterial strains which causes the diseases in human beings. We conclude that synthesis of gold nanoparticles by physical or chemical process is very toxic and cost effective when compared with biological synthesis, a better option for nanoparticles with high efficacy to antibacterial activity.